Pit and Fissure Sealant versus Fluoride Varnish for the Prevention of Dental Caries in School Children: A Systematic Review and Meta-Analysis - Tasneem Rashed; Nura Alkhalefa; Alaa Adam; Abdulaziz AlKheraif (International Journal of Clinical Practice)
Children’s dental health has become the main concern, due to the increase in caries prevalence amongst children. Pit and fissure sealant (PFS) and fluoride varnish (FV) are effective measures for preventing dental caries. However, the clinical efficacy of these interventions when compared to one another is uncertain. The aim of the present systematic review with meta-analysis was to compare pit and fissure sealants with fluoride varnish for caries prevention of first permanent molars among schoolchildren. This is a meta-Analysis, which involves randomized control trials that compare the effectiveness of PFS with FV within 24 months of follow-up. Five databases were searched from 1990 to 2019 to identify studies published in Arabic or English language. The risk ratio (RR) and 95% confidence intervals (CIs) were calculated using a random-effects model. A total number of 4 studies were included with overall of 1249 children in both groups. Three included trial reported caries increment of first permanent molars (FPM) with 24 months of follow-up, there was no statistical significance (RR: 0.65; 95% CI 0.31 to 1.35; P = 0.26 I2 = 89%). As regards DMFS increment, the analysis showed no statistical differences between FV and PFS in terms of lowering DMFS increment (MD: 0.09; 95% CI: −0.03 to 0.21). Findings of this meta-analysis proved there is no significant difference between PFS and FV in caries prevention efficacy of FPMs at 2 years’ follow-up, emphasizing the use of FV since it is more affordable and easier to apply.